Atomistic Assessment of Drug-Phospholipid Interactions Consequent to Cancer Treatment: A Study of Anthracycline Cardiotoxicity - Elsayed Ahmed, Yara (AUC Knowledge Fountain, 2023)
Despite being one of the most effective chemotherapeutic agents developed to date, Anthracyclines are notorious for their cardiotoxicity. Their clinical use is frequently limited both in dosage and in prescription due to the severe cardiac damage they cause. The mechanism of anthracycline-induced cardiotoxicity is not yet fully understood. However, it is hypothesized that interactions with the myocardial membrane play an important role in imparting cardiotoxicity. In this study, we use molecular dynamics simulations and density functional theory calculations to study the anthracycline drug molecules and the interactions that they have with the myocardial membrane. We construct a myocardial membrane model that incorporates key experimental findings from lipidomic studies in the literature. Our myocardial membrane model is more realistic and representative in terms of the phospholipid arrangement of the bilayer. For further validation, we compare our myocardial membrane model to another membrane model that consists of only one type of phospholipid that is frequently used in prior literature. With both membrane models, we examine the interactions of Doxorubicin, Epirubicin, Daunorubicin, and Idarubicin in three different molecular forms; pristine, major metabolite, and salt. We rank the anthracycline molecular forms from highest to lowest risk of cardiotoxicity in terms of (i) their residence time near the myocardial membrane’s surface, (ii) the average number of hydrogen bonds that anthracyclines form with the membrane, (iii) the immobilization of the molecule by the myocardial membrane’s surface, and lastly (iv) the location of the molecule with respect to the mid plane of the myocardial membrane. The resulting ranking of all the analyses combined show that salt forms have the highest probability of inducing cardiotoxicity, followed by the major metabolites then pristine forms. Moreover, the results from the location of the molecules from the mid plane of the membrane highlight the molecules’ general preference to the myocardial membrane’s upper layer. This finding suggests that the entry of the molecules into the cell through interactions with the upper\outer layer is possibly preferred to their exit through interactions with the lower\inner layer of the myocardial membrane, causing the anthracycline molecules to accumulate inside the myocyte. Lastly, we demonstrate that the more realistic myocardial membrane model was able to capture interactions that were otherwise not observed with the simpler model.